D4P4: A Neuro-Pedagogic Model for Developing High-Risk/ High-Precision Procedural Skills in Residency Training - Hermanto TJ (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Medical education stands at a pivotal juncture. The long-standing